Who Gets Served in Gifted Education? Demographic Representation and a Call for Action - Peters, Scott J.; Gentry, Marcia; Whiting, Gilman W.; McBee, Matthew T. (The Gifted child quarterly, 2019)
The disproportional representation of students from various demographic subgroups within identified gifted and talented populations has long frustrated policy makers, education advocates, researchers practitioners within the field, and those concerned with societal inequality in general. Despite the prevalence of articles in the media reporting on disproportional representation, little research has been conducted to track whether (a) the representation of these student subgroups, particularly students with limited English proficiency or students with disabilities, has changed over time or (b) states with and without policies differ in proportional representation of students identified with gifts and talents. For example, increasingly, gifted education advocates have pushed for mandates that all students be screened for gifted program eligibility as a way to combat disproportionality, despite little evidence that such methods influence proportionality. Therefore, this study sought to understand whether and how state and national gifted program demographics have changed over time and how proportionality is correlated with state mandates for gifted education identification or services. A preprint of this paper as well as additional figures are available at: https://osf.io/325m9/.